Direct ophthalmoscopy skills among Medical students (Research, Society and Development, 2022)
Direct ophthalmoscopy is part of physical examinations applied in patients; it is relevant for the diagnosis and prognosis of several diseases, since several systemic diseases lead to changes in the posterior segment of the eye. The aim of the present research is to investigate the ability of graduates in Medicine in recognizing changes in normal eye fundus deriving from illnesses that affect the human body. The adopted research methodology was based on direct ophthalmoscopy workshops carried out with 49 students; questionnaires with multiple choices alternatives about 8 images of funduscopic manifestations, 1 normal retinography and 7 images with systemic manifestations of prevalent diseases were applied. Results have shown little familiarity of some participants with the identification and differentiation of eye fundus normality based on the approached diseases. However, it was possible observing that participant students did not have much knowledge about normal eye fundus. Thus, they had difficulty in distinguishing different patterns of fundus outcomes compatible to their respective diseases. Nevertheless, they presented good knowledge on what is expected to find in normal eye fundus.